LetsGoFit unlocked: revolutionizing wellness with gamified mobile health / Siti Nurkhairina Yahizan … [et al.] - Yahizan, Siti Nurkhairina; Mat Zain, Nurul Hidayah; Abdul Razak, Fariza Hanis; Ismail, Ismassabah; Mohamed Noh, Nor Azida (Faculty of Computer and Mathematical Sciences, 2023)
Mobile applications have emerged as valuable tools to promote physical well-being in an era marked by the fusion of technology and health-conscious lifestyles. Despite the growing awareness of the importance of exercise and stretching in maintaining health, many women struggle to find accessible and personalized solutions to incorporate regular physical activity into their lives. Existing fitness apps often lack tailored stretching exercises for women, leading to a gap in addressing their unique physiological requirements. Therefore, we developed a women's stretching exercises application called LetsGoFit, which combines the convenience of mobile technology with the engaging elements of gamification to create a user-friendly and enjoyable exercise experience. The gamified mobile health implemented Rapid Application Development (RAD), providing a flexible and iterative approach to software development that emphasizes rapid prototyping and continuous feedback. The development of LetsGoFit is based on the GMHealth framework that consists of eight themes: Self-Representation, Self-Monitoring, Esteem, Enjoyment, Continuous, Guidance, Socializing and Improvement. In conclusion, LetsGoFit represents a novel approach to promoting women's health through a gamified mobile health application. The accessibility of a mobile application with aspects of gamification empowers women to maintain their stretching exercises, contributing to improved physical health and overall quality of life.